“SUSTAINABILITY- A SHARED PATH FOR FUTURE GENERATIONS” (International Journal of Food and Nutritional Sciences, 2021)
Sustainability represents a holistic framework aimed at meeting the needs of the present without compromising future generations' ability to meet their own. This multidimensional concept intertwines economic viability, social equity, and environmental health, highlighting the necessity for integrated approaches to address pressing global challenges such as climate change, resource depletion, and biodiversity loss. The urgency for sustainable practices is exacerbated by unsustainable consumption patterns, emphasizing the importance of transitioning to renewable resources, sustainable agriculture, and equitable social systems. This paper explores the definition and dimensions of sustainability, the three pillars that support it—people, planet, and profit—and the importance of resource conservation, climate change mitigation, and intergenerational equity. Challenges such as population growth, economic inequality, political instability, technological dependence, and consumerism hinder progress towards sustainability. Pathways for achieving sustainability include the United Nations Sustainable Development Goals (SDGs), community engagement, education, sustainable business practices, and innovative solutions. Case studies illustrate successful implementations of sustainable practices in various sectors, showcasing the potential for positive change. The future of sustainability necessitates global cooperation, youth activism, and the integration of sustainability into policy frameworks, emphasizing personal responsibility. Ultimately, sustainability is a shared path that requires collective action and innovation, recognizing the intricate connections between environmental, economic, and social systems.